ВИКОРИСТАННЯ ЕЛЕМЕНТІВ НАРОДОЗНАВСТВА В ПРОЦЕСІ ПІДГОТОВКИ МАЙБУТНІХ ІНЖЕНЕРІВ ТЕХНІЧНИХ ВНЗ (Педагогіка вищої та середньої школи, 2008)
The revival spiritual and moral is a necessity of time. In clause the conceptual principles of spiritual - moral education of the students by means of national knowledge are proved.